Physical properties of thermoplastic made from tacca leontopetaloides starch - Ab Wahab, Muhammad Azizi (2019)
Usage of thermoplastic made from renewable sources from plants has been a focus in research in recent years due to the potential of the product being usable in variable of method and industries because it is biodegradable and is seen as one of the possible method of reducing the amount of waste in landfills. This research focuses on the physical properties of tacca leontopetaloides/ethylene thermoplastic blend properties which are the shear stress and tensile strength respectively.